Noncoding RNA Regulation of Dopamine Signaling in Diseases of the Central Nervous System - Carrick, William T.; Burks, Brandi; Cairns, Murray J.; Kocerha, Jannet (Frontiers in Molecular Biosciences, 2016)
Dopaminergic neurotransmission mediates a majority of the vital central nervous system functions. Disruption of these synaptic events provokes a multitude of neurological pathologies, including Parkinson’s, schizophrenia, depression and addiction. Growing evidence supports a key role for noncoding RNA (ncRNA) regulation in the synapse. This review will discuss the role of both short and long ncRNAs in dopamine signaling, including bioinformatic examination of the pathways they target. Specifically, we focus on the contribution of ncRNAs to dopaminergic dysfunction in neurodegenerative as well as psychiatric disease.